Association of status of acetylcholinesterase and ACHE gene 3' UTR variants (rs17228602, rs17228616) with drug addiction vulnerability in pakistani population. (1st August 2019) - Javed, Tahira; Habib, Rabia; Ghafoor, Sania; Rumman, Baseerat; Awan, Sliha; Ntepe, Leonel J.M.; Batool, Sajida; Nurulain, Syed M.
Abstract: Substance addiction is a chronic, relapsing mental disorder Characterized by compulsive drug seeking, and loss of control over drug intake and relapse after prolonged abstinence. Genetics has been shown to contribute towards an individual's vulnerability to addiction. Acetylecholine (ACh), a cholinergic neurotransmitter hydrolyzed by acetylcholinesterase (AChE), is an essential neurotransmitter and neuromodulator in central and peripheral nervous system and has regulatory influence on numerous neuronal functions including addiction. The present study was carried out to investigate the role of acetylcholinesterase (AChE) in addiction through measurement of enzyme activity and to find potential association of ACHE gene 3′UTR variants rs17228602 and rs17228616 in heroin, hashish and poly drug addicts. Both SNPs are located within microRNA (miRNA) recognition sites with potential to affect miRNA/transcript interaction. A total of 122 addicts of heroin, hashish and polydrug were recruited from local rehabilitation centers to participate in this study. AChE activity was measured in blood by Ellman's method. SNP genotyping was performed by restriction fragment length polymorphism (PCR-RFLP) and Sanger sequencing. The AChE activity was found significantly higher (p ≤ 0.005) in addicted cohort (mean ± standard error of mean 0.020 ± 0.001 μmol/L/min; 95% confidence interval (CI) 0.018–0.022) in comparison to non-addicted healthy subjects (0.011 ± 0.001 μmol/L/min; 95% confidence interval CI 0.010–0.013). A statistically significant association of ACHE rs17228602 SNP with addiction vulnerability in dominant (DM: Odd's ratio OR = 2.095, 95% CI = 1.157–3.807 p = 0.009) and allelic genetic models (OR = 1.854 95% CI = 1.082–3.187, p = 0.016) was observed. However, no statistically significant association of rs17228616 SNP with substance abuse disorder was found. The data presented here shows that AChE could play significant role in substance addiction. Further studies with larger sample size and other variants of AChE are recommended to identify novel therapeutic approaches for cholinergic based treatment of addiction. Highlights: Increased AChE enzymatic activity was observed in addicted cases. Significant association of ACHE 3′UTR SNP with addiction vulnerability identified. The location of tested SNP affects miRNA binding site. Overall, the presented data shows involvement of AChE in substance addiction.